2017
DOI: 10.1101/112912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the causal role of body mass index on cardiovascular health in young adults: Mendelian randomization and recall-by-genotype analyses

Abstract: BackgroundMendelian randomization (MR) studies of body mass index (BMI) and cardiovascular health in mid-to-late life suggest causal relationships, but the nature of these has not been explored systematically at younger ages. Using complementary MR and recall-by-genotype (RbG) methodologies, our objective was to estimate the causal effect of BMI on detailed measures of cardiovascular health in a population of young healthy adults.Methods and FindingsData from the Avon Longitudinal Study of Parents and Children… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 62 publications
5
23
1
Order By: Relevance
“…not certified by peer review) (which was The copyright holder for this preprint this version posted October 10, 2019. . https://doi.org/10.1101/19008474 doi: medRxiv preprint causally related to higher LVMI, suggesting that there is meaningful variation in cardiac structure measures in early adulthood that is likely to track across life and relate to later life cardiovascular health (36). Nevertheless, in the current study the positive association between childhood BPV and LVMI in early adulthood did not persist once childhood mean BP had been adjusted for.…”
Section: Such a Positive Correlation Has Been Characterised In Studiecontrasting
confidence: 53%
“…not certified by peer review) (which was The copyright holder for this preprint this version posted October 10, 2019. . https://doi.org/10.1101/19008474 doi: medRxiv preprint causally related to higher LVMI, suggesting that there is meaningful variation in cardiac structure measures in early adulthood that is likely to track across life and relate to later life cardiovascular health (36). Nevertheless, in the current study the positive association between childhood BPV and LVMI in early adulthood did not persist once childhood mean BP had been adjusted for.…”
Section: Such a Positive Correlation Has Been Characterised In Studiecontrasting
confidence: 53%
“…23 Young people might not yet have accumulated these risk factors, and accordingly, they are an optimal study population in this regard. Childhood obesity has, however, independently been associated with significant changes in myocardial geometry and function, 24 which has been further strengthened in a study of obesity genes in young adults, 25 indicating an early onset of potentially unfavorable alterations in the myocardium that are independent of other cardiovascular risk factors. In this study, we found that the risk of cardiomyopathy started to increase at levels of adolescent BMI at the upper normal level, which is in accordance with recent findings with respect to early heart failure 7 and is supported by the findings by Twig et al 10 In studies of people with severe obesity, cardiomyopathy has been identified as a complication, 26,27 with severity and duration of obesity recognized as essential determinants of alterations in cardiac performance and morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Whether puberty timing is a concern for cardiometabolic health in populations, however, depends on whether it is truly causal. Higher adiposity in childhood may induce an earlier puberty [ 8 ] and track forward into adulthood [ 9 13 ], making it an important potential confounder. Prospective studies of puberty timing in relation to cardiometabolic outcomes tend not to account for differences in pre-pubertal adiposity [ 14 , 15 ], and the few studies that do often find substantial attenuation of puberty–outcome associations [ 4 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%